Exploring Critical and Ethnopedagogical Dimensions in Living Museums: Ethnographic Perspectives in Cultural Education Practices - Rahman Abidin; Nana Supriatna; Didin Saripudin; Leli Yulifar (STKIP Singkawang, 2024)
Living museum is a concept that integrates direct experience with cultural and historical learning. This article explores the critical and ethnopedagogical dimensions in living museum practices with a focus on ethnographic perspectives in cultural education. Through a qualitative approach that includes participant observation, in-depth interviews, and document analysis, this study aims to understand how living museums can function as educational spaces that not only present history, but also encourage critical thinking and cultural reflection among visitors. This study identifies that living museums provide a platform for interactive dialogue between visitors and the cultural practices presented. In this context, living museums are not only places to display artifacts, but also arenas for knowledge exchange that involve community members in the educational process. This study highlights how an ethnopedagogical approach, involving guides as cultural stakeholders, can deepen visitors' understanding of cultural heritage and history. The findings of this study suggest that living museums can function as tools for critical thinking and cultural education, by encouraging visitors to reflect on the social and historical contexts of the artifacts they see. In addition, this study shows that living museums that successfully integrate ethnopedagogical approaches can create immersive and sustainable experiences for visitors, which go beyond mere historical education to embrace broader discussions about cultural identity and social values.